The Influence of Log Defects on the Cutting Yield of Oak Venner - MUȘAT Elena Camelia (BioResources, 2018)
The quality of logs entering the production line is important because it controls the quality and yield of veneer. In Romania, Quercus species represent 18% of the total forests, and of which 2% is exclusively the pedunculate oak. The wood of pedunculate oak is hard and elastic, and it has a good natural durability. Due to such features it also has multiple uses in the furniture industry, construction, joinery, and cooperage works. The present work highlights the influence of some characteristics of the raw material on the cutting yield of veneer in the case of pedunculate oak logs purchased from different regions. Defects in the raw material had a certain negative influence on the veneer quality. The defects were identified and prioritized using the Pareto diagram.
Keywords: Oak; Log defects; Veneer; Yield; Pareto diagram